A mortalidade por traumas relacionados a acidentes automobilísticos no Brasil: uma revisão de literatura - BARRETO JUNIOR, Ismael Ferreira (2024)
Introduction: traffic accidents represent a delicate health issue in Brazil, killing many people each year and leaving many others with disability or permanent sequelae. Objective: to carry out an integrative literature review that allows answering the question: how does mortality from car accidents appear in different locations in Brazil? Methodology: In order to achieve the objectives, an integrative literature review was carried out, in order to obtain information concerning the theme of this work. The search platform chosen was the Scopus base, and the PRISMA flowchart was used to sort publications. Results: after a bibliographic search, 17 articles were selected to compose the body of the work. Conclusions: there is an increasing number of deaths in practically all the studies analyzed, and the highest number of accidents that lead to death correspond to young men of active working age.